Influenza Vaccine Effectiveness Against All-Cause Mortality Following Laboratory-Confirmed Influenza in Older Adults, 2010–2011 to 2015–2016 Seasons in Ontario, Canada. (23rd December 2020) - Chung, Hannah; Buchan, Sarah A; Campigotto, Aaron; Campitelli, Michael A; Crowcroft, Natasha S; Dubey, Vinita; Gubbay, Jonathan B; Karnauchow, Timothy; Katz, Kevin; McGeer, Allison J; McNally, J Dayre; Mubareka, Samira; et al.
Abstract: Background: Older adults are at increased risk of mortality from influenza infections. We estimated influenza vaccine effectiveness (VE) against mortality following laboratory-confirmed influenza. Methods: Using a test-negative design study and linked laboratory and health administrative databases in Ontario, Canada, we estimated VE against all-cause mortality following laboratory-confirmed influenza for community-dwelling adults aged >65 years during the 2010–2011 to 2015–2016 influenza seasons. Results: Among 54 116 older adults tested for influenza across the 6 seasons, 6837 died within 30 days of specimen collection. Thirteen percent (925 individuals) tested positive for influenza, and 50.6% were considered vaccinated for that season. Only 23.2% of influenza test-positive cases had influenza recorded as their underlying cause of death. Before and after multivariable adjustment, we estimated VE against all-cause mortality following laboratory-confirmed influenza to be 20% (95% confidence interval [CI], 8%–30%) and 20% (95% CI, 7%–30%), respectively. This estimate increased to 34% after correcting for influenza vaccination exposure misclassification. We observed significant VE against deaths following influenza confirmation during 2014–2015 (VE = 26% [95% CI, 5%–42%]). We also observed significant VE against deaths following confirmation of influenza A/H1N1 and A/H3N2, and against deaths with COPD as the underlying cause. Conclusions: These results support the importance of influenza vaccination in older adults, who account for most influenza-associated deaths annually. Abstract : Using the test-negative design and linked databases, influenza vaccine effectiveness against all-cause mortality within 30 days of influenza testing was 20%, increasing to 34% after correcting for exposure misclassification. Therefore, vaccination may prevent deaths following influenza infection in older adults.